Coaxial Manganese Dioxide@N-doped Carbon Nanotubes as Superior Anodes for Lithium Ion Batteries. (10th November 2015) - Yue, Jie; Gu, Xin; Jiang, Xiaolei; Chen, Liang; Wang, Nana; Yang, Jian; Ma, Xiaojian
Graphical abstract: Highlights: MnO2 @N-dopedcarbonnanotube(N-CNT) composites are prepared by a facile process. MnO2 @N-CNT anodes exhibit better electrochemical properties than MnO2 @CNT. MnO2 @N-CNT anodes show a capacity of 1415 mAh g −1 at 100 mA g −1 after 150 cycles. Abstract: Carbon nanotube (CNT) has been widely applied to transition metal oxides anodes for lithium ion batteries, acting as a buffer, hollow backbone and conductive additive. Since the presence of N in carbon materials can enhance the reactivity and electrical conductivity, N-doped carbon nanotube (N-CNT) might be a better choice than pure CNT, which is exemplified by coaxial manganese dioxide@N-doped carbon nanotubes as a superior anode. The electrochemical properties of MnO2 @N-CNT are investigated in terms of cycling stability and rate capability. The nanocomposite can deliver a specific capacity of 1415 mAh g −1 after 100 cycles at the current density of 100 mA g −1, which is better than that of MnO2 @commercial CNT and MnO2 . The excellent performance might be related to the integration of hollow structure, one-dimensional nanoscale size as well as combination with N-doped carbon materials.